Dynamic Stress-Strain Behaviour of Steel Fiber Reinforced High-Performance Concrete with Fly Ash - Tan Chien Yet; R. Hamid; Mudiono Kasmuri (Advances in Civil Engineering)
The addition of steel fibers into concrete mix can significantly improve the engineering properties of concrete. The mechanical behaviors of steel fiber reinforced high-performance concrete with fly ash (SFRHPFAC) are studied in this paper through both static compression test and dynamic impact test. Cylindrical and cube specimens with three volume fractions of end-hooked steel fibers with volume fraction of 0.5%, 1.0%, and 1.5% (39.25, 78.50, and 117.75 kg/m3) and aspect ratio of 64 are used. These specimens are then tested for static compression and for dynamic impact by split Hopkinson pressure bar (SHPB) at strain rate of 30–60 s−1. The results reveal that the failure mode of concrete considerably changes from brittle to ductile with the addition of steel fibers. The plain concrete may fail under low-strain-rate single impact whereas the fibrous concrete can resist impact at high strain rate loading. It is shown that strain rate has great influence on concrete strength. Besides, toughness energy is proportional to the fiber content in both static and dynamic compressions.